DETERMINATION OF ANTIFUNGAL AND ANTIOXIDANT POTENTIAL OF LEAF AND FRUIT EXTRACTS OF GUAVA (Psidium guajava Linn.) (Applied Biological Research, 2024)
The present study was aimed to evaluate the antifungal and antioxidant   properties of leaf and fruit extracts of guava (Psidium guajava Linn.). Antifungal   assays were conducted to assess the efficacy of extracts against clinically relevant   fungal strains, viz., Aspergillus niger MTCC-4325, Penicillium chrysogenum  MTCC-2539, Candida albicans MTCC-7315, and Fusarium solani MTCC-3309.   Besides, enzyme activity for catalase (CAT) and peroxidase (POD) were assayed  to elucidate the antioxidant potential of extracts. The radical scavenging   activities of extracts were determined using 2,2-diphenyl-1-picrylhydrazyl   (DPPH), and ferric reducing antioxidant power (FRAP) assays to quantify the  overall antioxidant capacity. Results indicated pronounced inhibitory activity   against F. solani in methanolic extracts of leaves (21.66 ± 2.05) and fruits (24.66  ± 1.25), with aqueous extracts exhibiting comparatively lesser inhibition across   the tested fungal strains. Moreover, the enzyme activity assays revealed higher  CAT and POD activities in fresh leaf extract as compared to the fruit extract.   Notably, DPPH assay underscored the superior antioxidant potential of Psidium  leaf extracts relative to fruit extracts, while FRAP assay showed higher radical   scavenging capacity of methanolic extract as compared to the aqueous extract.
Keywords: Antifungal; antioxidant; CAT; DPPH; extracts; FRAP; POD